International law and its others - Orford, Anne (Cambridge University Press, 2006)
Institutional and political developments since the end of the Cold War have led to a revival of public interest in, and anxiety about, international law. Liberal international law is appealed to as offering a means of constraining power and as representing universal values. This book brings together scholars who draw on jurisprudence, philosophy, legal history and political theory to analyse the stakes of this turn towards international law. Contributors explore the history of relations between international law and those it defines as other - other traditions, other logics, other forces, and other groups. They explore the archive of international law as a record of attempts by scholars, bureaucrats, decision-makers and legal professionals to think about what happens to law at the limits of modern political organisation. The result is a rich array of responses to the question of what it means to speak and write about international law in our time.